PERKEMBANGAN JIWA KEAGAMAAN PADA ANAK DAN REMAJA - Sukatin - (HIKMAH: JURNAL PENDIDIKAN AGAMA ISLAM, 2018)
Development of religious spirit in children and adolescents, which according to Zakiyah Darajat that the spirit of religion in children and adolescents develops along with their physical and psychological development. While in the context of educating children and adolescents, parents and educators must understand and know the development of religion well in children and adolescents. Development can be interpreted as “progressive and continuous changes in individuals from birth to death”. Stage of religious development in children through three stages, namely; (1) The Fairly Tale Stage; (2) The Realistic Stage; (3) The Individual Stage. The factors that influence it are: (1) Family education;(2) Educational institutions;(3) Community education. The development of the soul of religion in adolescence is strongly influenced by the development of their psychological aspects, social considerations, development of feelings, development of morals, attitudes and interests are also influenced by other factors such as; internal factors (heredity, age, psychiatric disorders, and personality) and external (family, institutional, and community).